Combined application of spiral computed tomography and transrectal ultrasound in the evaluation of neoadjuvant chemoradiotherapy in rectal cancer - L. M. Vasko; T. O. Zhukova; V. F. Pocherniaieva; O. V. Kornieiev (Zaporožskij Medicinskij Žurnal)
Aim. To study the possibilities of spiral computed tomography and transrectal ultrasound using for the evaluation of neoadjuvant chemoradiotherapy effectiveness in patients with locally advanced rectal cancer in order to expand opportunities for sphincter-preserving surgery.